Management of fresh odontoid fractures using posterior C1-2 fixation without fusion: a long-term clinical follow-up study - Ma, Fei; Fan, Yuanhe; Liao, Yehui; Tang, Qiang; Tang, Chao; Xu, Shicai; Wang, Qing; Lan, Yongshu; Zhong, Dejun (Journal of neurosurgery. Spine, 2022)
Posterior C1-2 fixation without fusion makes it possible to restore atlantoaxial motion after removing the implant, and it has been used as an alternative technique for odontoid fractures; however, the long-term efficacy of this technique remains uncertain. The purpose of the present study was to explore the long-term follow-up outcomes of patients with odontoid fractures who underwent posterior C1-2 fixation without fusion. A retrospective study was performed on 62 patients with type II/III fresh odontoid fractures who underwent posterior C1-2 fixation without fusion and were followed up for more than 5 years. The patients were divided into group A (23 patients with implant removal) and group B (39 patients without implant removal) based on whether they underwent a second surgery to remove the implant. The clinical outcomes were recorded and compared between the two groups. In group A, the range of motion (ROM) of C1-2 was calculated, and correlation analysis was performed to explore the factors that influence the ROM of C1-2. A solid fracture fusion was found in all patients. At the final follow-up, no significant difference was found in visual analog scale score or American Spinal Injury Association Impairment Scale score between the two groups (p > 0.05), but patients in group A had a lower Neck Disability Index score and milder neck stiffness than did patients in group B (p < 0.05). In group A, 87.0% (20/23) of the patients had atlantoodontoid joint osteoarthritis at the final follow-up. In group A, the C1-2 ROM in rotation was 6.1° ± 4.5° at the final follow-up, whereas the C1-2 ROM in flexion-extension was 1.8° ± 1.2°. A negative correlation was found between the C1-2 ROM in rotation and the severity of tissue injury in the atlantoaxial region (r = -0.403, p = 0.024) and the degeneration of the atlantoodontoid joint (r = -0.586, p = 0.001). Posterior C1-2 fixation without fusion can be used effectively for the management of fresh odontoid fractures. The removal of the implant can further improve the clinical efficacy, but satisfactory atlantoaxial motion cannot be maintained for a long time after implant removal. A surgeon should reconsider the contribution of posterior C1-2 fixation without fusion and secondary implant removal in preserving atlantoaxial mobility for patients with fresh odontoid fractures.